Ефекат раног нивоа серумског протеина који везује хепарин (ХБП) на појаву сепсе код пацијената са тешким опекотинама: HBP levels on occurrence of sepsis in patients with severe burns - Xiang, Lihan; Yang, Guimei; Lou, Liming; Lv, Le; Zheng, Liyuan; Zhang, Caixia; He, Qian (Journal of Medical Biochemistry, 2025)
[Objective] To evaluate the expression levels of early serum heparin-binding protein (HBP) in patients with severe burns and investigate its prognostic significance and predictive utility for sepsis development. [Methods] The clinical data of 52 patients with severe burns who were admitted to our hospital between January 2023 and May 2025 were retrospectively analyzed. General information, including the patient’s age, sex, body mass index (BMI), total burn area, and tracheal intubation or tracheotomy, was collected. Within 48 hours of the patient’s admission, the patient’s blood pressure, white blood cell count, serum procalcitonin (PCT), and serum C reactive protein (CRP) level were measured. The second assessment of acute physiology and chronic health within 48 hours of admission included the results of the sequential organ failure assessment (SOFA) and APACHE II. The patients were separated into two groups on the basis of their conditions at discharge: the nonsurviving group and the surviving group. [Results] Compared with the nonsepsis group (8.2 ng/mL), the sepsis group had a considerably greater median early serum HBP level (20.8 ng/mL) (P<0.001). The area under the curve (AUC) of HBP for sepsis prediction, according to the ROC curve analysis, was 0.87 (95% CI: 0.82–0.92). The sensitivity was 85.0%, and the specificity was 82.1% at the cutoff value of 14.6 ng/mL. After controlling for confounding variables such burn area and inhalation injury, multivariate logistic regression analysis verified that HBP>14.6 ng/mL was an independent risk factor for the development of sepsis (OR=4.53, 95% CI: 2.67–7.69). According to survival analysis, patients in the high-HBP group had a significantly greater 28-day mortality rate (log-rank P<0.01). Patients in the death group were older than those in the survival group were, and this difference was statistically significant (P=0.036). The area under the ROC curve (AUC) of the HBP level for predicting patient death during hospitalization was 0.798; its sensitivity and specificity were 88.33% and 70.00%, respectively, for HBP≥147.03 ng/mL. In patients with sepsis following severe burns, the AUC of the HBP level for the prediction of septic shock was 0.789. Its sensitivity and specificity were 90.00% and 63.20%, respectively, when the HBP concentration was greater than 147.03 ng/mL. [Conclusion] The significantly elevated serum HBP level in patients with severe burns in the early stage is closely related to the risk of sepsis, and it can be used as a sensitive biomarker for early warning of sepsis.